Divergent approach to the synthesis of (-)-balanol heterocycle and cis-3-hydroxypipecolic acid based on chiral 2-aminoalkanol equivalent - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron, 2021)
Enantioselective synthesis of the hexahydroazepine core of (-)-balanol and formal synthesis of cis-3hydroxypipecolic acid from a common intermediate have been accomplished by a divergent path. The common intermediate was accessed from a favorably protected enantiomerically pure 2-amino-1,3,4-butanetriol (ABT) equivalent via oxidation and Wittig olefination. The synthesis of (-)-balanol heterocycle featured tandem reduction/acetal-deprotection/gamma-lactonization reaction and a one-pot azide reduction followed by seven membered aza-heterocycle formation while the route to cis-3-hydroxypipecolic acid highlighted the base induced piperidine ring formation and regioselective benzylidine-acetal cleavage. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Amino-alcohol; desymmetrization; Hexahydroazepine; Piperidine alkaloids; Protein kinase